Therapy of Small Cell Lung Cancer (SCLC) with a Topoisomerase-I-inhibiting Antibody-Drug Conjugate (ADC) Targeting Trop-2, Sacituzumab Govitecan - Gray, Jhanelle E; Heist, Rebecca S; Starodub, Alexander N; Camidge, D Ross; Kio, Ebenezer A; Masters, Gregory A; Purcell, W Thomas; Guarino, Michael J; Misleh, Jamal; Schneider, Charles J; Schneider, Bryan J; Ocean, Allyson; et al. (Clinical cancer research, 2017)
We evaluated a Trop-2-targeting antibody conjugated with SN-38 in metastatic small cell lung cancer (mSCLC) patients. Sacituzumab govitecan was studied in patients with pretreated (median, 2; range, 1-7) mSCLC who received either 8 or 10 mg/kg i.v. on days 1 and 8 of 21-day cycles. The primary endpoints were safety and objective response rate (ORR); duration of response, progression-free survival (PFS), and overall survival (OS) were secondary endpoints. Sixty percent of patients showed tumor shrinkage from baseline CTs. On an intention-to-treat basis ( = 50), the ORR was 14% (17% for the 10-mg/kg group); the median response duration, 5.7 months; the clinical benefit rate (CBR ≥4 months), 34%; median PFS, 3.7 months; and median OS, 7.5 months. There was a suggested improvement in PR, CBR, and PFS with sacituzumab govitecan in second-line patients who were sensitive to first-line therapy, but no difference between first-line chemosensitive versus chemoresistant patients in the overall population. There was a statistically significant higher OS in those patients who received prior topotecan versus no topotecan therapy in a small subgroup. Grade ≥3 adverse events included neutropenia (34%), fatigue (13%), diarrhea (9%), and anemia (6%). Trop-2 tumor staining was not required for patient selection. No antibodies to the drug conjugate or its components were detected on serial blood collections. Sacituzumab govitecan appears to have a safe and effective therapeutic profile in heavily pretreated mSCLC patients, including those who are chemosensitive or chemoresistant to first-line chemotherapy. Additional studies as a monotherapy or combination therapy are warranted. .